(untitled) (Research, Society and Development, 2020)
The objective of this work was to develop roll bread with partial replacement of wheat flour by malt bagasse (MB) and to evaluate the changes in their physical-chemical characteristics and microbiological parameters. Four formulations of breads were elaborated: one control without MB, and 3 formulations with partial replacement of wheat flour varying the MB amount in 5, 10 and 15%. MB reduced the carbohydrate content of the dough; consequently, the calories of the bread rolls were also reduced. On the other hand, moisture, minerals and lipids contents were increased. The type of protein changed with the substitution of MB in the dough, but the amount of proteins was not altered. The lowest hardness values were observed in breads with 5% and 10% MB, being related to higher values of acidity in the dough. The increase in the mineral content of the dough was related to the darkening of the bread. All bread formulations showed microbiological quality within the limits established by Brazilian legislation for coliforms at 45 °C, Bacillus cereus and Salmonella sp. The formulation with 10% MB resulted in bread rolls with higher nutritional value, in terms of minerals, lower hardness and with a darker aspect all around when compared to the control bread, giving it an aspect of wholegrain bread.